A search for Lorentz and CPT violation in the neutrino sector of the standard model extension using the near detectors of the Tokai to Kamioka neutrino oscillation experiment - Clifton, Gary Alexander, author; Toki, Walter, advisor; Berger, Bruce, committee member; Eykholt, Richard, committee member; Hulpke, Alexander, committee member (Colorado State University. Libraries, 2016)
The Tokai to Kamioka (T2K) neutrino experiment is designed to search for electron neutrino appearance oscillations and muon neutrino disappearance oscillations. While the main physics goals of T2K fall into conventional physics, T2K may be used to search for more exotic physics. One exotic physics analysis that can be performed is a search for Lorentz and CPT symmetry violation (LV and CPTV) through short baseline neutrino oscillations. The theoretical framework which describes these phenomena is the Standard Model Extension (SME). Due to its off-axis nature, T2K has two near detectors. A search for LV and CPTV is performed in each detector. The search utilizes charged-current inclusive (CC inclusive) neutrino events to search for sidereal variations in the neutrino event rate at each detector. Two methods are developed; the first being a Fast Fourier Transform method to perform a hypothesis test of the data with a set of 10,000 toy Monte-Carlo simulations that do not have any LV signal in them. The second is a binned likelihood fit. Using three data sets, both analysis methods are consistent with no sidereal variations. One set of data is used to calculate upper limits on combinations of the SME coefficients while the other two are used to constrain the SME coefficients directly. Despite not seeing any indication of LV in the T2K near detectors, the upper limits provided are useful for the theoretical field to continue improving theories which include LV and CPTV.